(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Glass fiber reinforced polymer (GFRP) Rebar ‘s has an innovative material it’s been a potential application in construction practices due to its high tensile strength, corrosive resistance ease in its applications and relatively simple construction technique. To tap such potential, the existing body of knowledge on GFRP must be expanded to provide a proper basis for officials to add this method of construction to the provisions of the building code. This thesis aims to add to that body of knowledge through experimental investigation on performance of Glass fibre reinforced bar in compression members. Load carrying capacities of long and short columns reinforced longitudinally with glass fiber reinforced polymer rebar and laterally with steel bar were compared with steel reinforcement in this research. Test series consisted of columns having 150 Ø mm diameter and 660 mm length of 3 short columns. The main study in this program is on replacing the longitudinal reinforcement partially with GFRP bars and cement replaced by 20% with silica fume. Comparing such differently reinforced column with fully steel reinforced and GFRP reinforced columns. Load carrying capacities and failure behaviour of columns were observed by experimental investigation and compared with theoretical values. From the obtained results, it is observed that the replacement in longitudinal reinforcement partially with GFRP bars in short & long columns show the higher load carrying capacities. And the failure of the column is changed for the short columns